The impact of internal supervision and leadership on employee performance at the social service office - Marselino Wau; Alwinda Manao; Yohanes Dakhi (Institute of Computer Science (IOCS), 2023)
This research is quantitative and uses Smart PLS 4 in a causal design. The study used samples drawn from the entire workforce and was carried out at the Office of Social Affairs in South Nias Regency. A survey that was given to all employees served as the research tool, and version 4 of the SmartPLS data analysis program was used to analyze the results. The purpose of this study was to investigate the hypothesis that employee performance is influenced by internal supervision and leadership. According to the results of the external model testing, each variable was valid because its factor loading was greater than 0.70. All variables passed the reliability tests using Cronbach's alpha and composite reliability, with Cronbach's alpha values ranging from 0 to 767 and 0 to 891 and 0 to 842, respectively. A high level of measurement quality was indicated by the average variance extracted (AVE), which was greater than 0.50. Testing for discriminant validity also met the requirements, demonstrating that the measurements could differentiate between various constructs. Overall, the study discovered that internal supervision and leadership have a positive and significant impact on worker performance. These results are in agreement with the study's tested hypothesis. It is significant to note that the study has some limitations, including the use of a saturated sample and a focus on just two variables that affect employee performance. However, by enhancing leadership and internal supervision practices, this study adds to the body of knowledge on organizational behavior and offers managers insights into how to improve employee performance.